Franz Brentano: o conceito, o objeto e o método de uma "psicologia do ponto de vista empírico" - Petry, Ana Maris (2012)
This work aims to present the program of an empirical psychology of Franz Brentano, identifying the author's fundamental contributions to the foundation of a psychological science. When psychology sought autonomy of the philosophy and recognition as a positive science, it was necessary to: distinguish psychic phenomena of physical phenomena, to justify the distinction of the psychology of physiology; to clarify the concept of psyche, to justify an autonomy of psychology in relation to the philosophy; and also, identify a methodological access such research objects as an alternative to introspection, a possibility strongly opposed not only by positivism, but also by Hume and Kant. Without a clear and distinct definition of such concepts a psychological science would not be possible. Starting from the 19th century scientific historical context, this text introduces the concept of an empirical psychology, the research object of this discipline and the method established for such study as were defined by Brentano. The text follows the development of work Psychology from an empirical standpoint, published in 1874. This is a review of this crucial work of Brentano, showing its key concepts. The particular Brentano s conception of phenomenon and the identification of intentionality as fundamental characteristic of psychic phenomena enable Brentano to define the project of a psychological science that follows the science positivist criteria and, at the same time to avoid a mere phenomenical psychology